Labour market performance in OECD countries: A comprehensive empirical modelling approach of institutional interdependencies - Andreas Sachs; Frauke Schleer (WWWforEurope, 2013)
Reducing institutional rigidities in product and labour markets is key to lowering unemployment. The impact of such labour and product market reforms, however, depends crucially on the country-specific regulatory framework. In this paper, we estimate the country-specific impact of changes in six categories of institutional regulation conditional on the country-specific regulatory environment for a dynamic panel of 26 OECD countries. We overcome existing problems of modelling a large set of institutional interdependencies by applying a model selection approach which is innovative within this literature. In doing so, we provide evidence for the existence of higher-order institutional interdependencies. We further document that especially for changes in employment protection and the unemployment benefit system the impact on unemployment is mixed across countries, thus questioning the relevance of best-practice policies.
Keywords: C33; E02; E24; 330; labour market institution; institutional interdependencies; model selection; heuristic optimization